2020
DOI: 10.1101/2020.03.24.006379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenetic downregulation of HER2 during EMT leads to tumor resistance to HER2-targeted therapies in breast cancer

Abstract: HER2 receptor tyrosine kinase (encoded by ERBB2 gene) is overexpressed in approximately 25% of all breast cancer tumors (known as HER2-positive breast cancers). Overexpression of HER2 causes overactivation of downstream receptor tyrosine kinase pathways including PI3K/Akt and MAPK pathways and is a poor prognosis factor in breast cancer. Tyrosine kinase inhibitor lapatinib and anti-HER2 monoclonal antibodies trastuzumab and pertuzumab are FDA-approved HER2-targeted drugs for treatment of HER2-positive breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…The results of the current study showed a highly statistical significant association between high score and strong intensity of expression of Her 2 neu and low score and mild intensity of expression of N-cadherin. These results agree with those of Nami et al, (2020) who detected negative correlation between EMT markers and Her 2 neu expression in breast carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…The results of the current study showed a highly statistical significant association between high score and strong intensity of expression of Her 2 neu and low score and mild intensity of expression of N-cadherin. These results agree with those of Nami et al, (2020) who detected negative correlation between EMT markers and Her 2 neu expression in breast carcinoma.…”
Section: Discussionsupporting
confidence: 92%
“…These cell lines represent various types of ductal carcinoma (BT-474, HCC202, HCC1954, and MCF7) and adenocarcinoma (MDA-MB-231) and were selected on the basis of their expression levels of EpCAM and HER2. The BT-474, HCC202, and HCC1954 cell lines are all EpCAM and HER2 positive (35,36). The MCF7 cell line is EpCAM-positive, with a low HER2 expression, and the MDA-MB-231 cell line is both EpCAM and HER2 negative (35,37).…”
Section: Selection Of Tumor Cell Linesmentioning
confidence: 99%
“…This indicates that in spite of its effectiveness in the elimination of cancer cells, EpCAMtargeted DARPin is not a useful tool to eliminate breast cancer cells from ovarian cortex tissue. We therefore focused on HER2, a transmembrane protein frequently overexpressed in breast cancer cells (35,36). The HER2 protein is not expressed at detectable levels in ovarian cortex tissue (49) and is therefore a potential target for purging with an HER2-targeted DARPin fused to ETA.…”
Section: Purging Ovarian Cortex Tissue Of Breast Cancermentioning
confidence: 99%